RENEWAL OF LEGAL POLITICS OF INTERNATIONAL AGREEMENTS CONCERNING INDONESIA'S LOAN AGREEMENT TO ACHIEVE SUSTAINABLE DEVELOPMENT - Sumartini, Siti (Yustisia, 2018)
The government loan agreement is a tool or mechanism to generate capital, and as a source of national development financing as set forth in the RAPBN framework. However, it is practically reviewed that the status of the foreign loan agreement is inconsistent with existing laws and regulations, in particular Law No.24 of 2000 on the International Agreement (Treaty). In the provisions of the law foreign borrowing is one aspect that is subject to the criteria as an international agreement, whereas in the implementation of the G to G government loan agreement tends to use the international private legal system. In addition, loan agreement clauses often do not accommodate the debtor country's interest in realizing sustainable development. Therefore, a legal political renewal related to the loan agreement is required to fulfill the legal certainty element and can accommodate the national interest.